2013
DOI: 10.1002/ieam.1387
|View full text |Cite
|
Sign up to set email alerts
|

The relative sensitivity of macrophyte and algal species to herbicides and fungicides: An analysis using species sensitivity distributions

Abstract: Lemna spp. are the standard test species representing aquatic macrophytes in the current risk assessment schemes for herbicides and plant growth regulators in the European Union and North America. At a Society of Environmental Toxicology and Chemistry (SETAC) 2008 workshop on Aquatic Macrophyte Risk Assessment for Pesticides (AMRAP), a Species Sensitivity Distribution (SSD) working group was formed to address uncertainties about the sensitivity of Lemna spp. relative to other aquatic macrophyte species. For 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 13 publications
1
30
2
Order By: Relevance
“…The PPR Panel suggests, as a pragmatic approach, to perform a test on a dicot macrophyte when terrestrial dicot species are more than a factor of 10 more sensitive than monocot terrestrial species. Following the results of the SSD analysis reported in the paper by Giddings et al (2013), Myriophyllum spicatum should be a preferable dicot species to test additionally. The AMRAP document (Maltby et al, 2010) recommends the use of growth rate endpoints for macrophytes.…”
Section: Standard Toxicity Tests With Macrophytesmentioning
confidence: 91%
See 2 more Smart Citations
“…The PPR Panel suggests, as a pragmatic approach, to perform a test on a dicot macrophyte when terrestrial dicot species are more than a factor of 10 more sensitive than monocot terrestrial species. Following the results of the SSD analysis reported in the paper by Giddings et al (2013), Myriophyllum spicatum should be a preferable dicot species to test additionally. The AMRAP document (Maltby et al, 2010) recommends the use of growth rate endpoints for macrophytes.…”
Section: Standard Toxicity Tests With Macrophytesmentioning
confidence: 91%
“…An analysis using SSDs by Giddings et al (2013) indicated that neither Lemna gibba nor Myriophyllum spicatum is consistently among the most sensitive macrophyte species for all the herbicides and fungicides included in their analysis. The L. gibba EC 50 is within a factor of 10 of the HC 5 of the macrophyte SSD for 6 of 11 chemicals investigated, indicating that RA based on Lemna 31 If in one or more of the screening or efficacy tests with vascular plant species showing 50 phytotoxic effects at the maximum recommended application rate (MRR) or higher, the a.s. is considered to have herbicidal activity (see EPPO scheme for higher plants (EPPO, 2003)).…”
Section: Standard Toxicity Tests With Macrophytesmentioning
confidence: 97%
See 1 more Smart Citation
“…Species sensitivity distributions integrate the results of laboratory toxicity experiments with a least 8 species to estimate hazardous concentrations (HC x values) for a given fraction of species [9]. Microcosm and mesocosm studies represent tier 3 of the risk assessment [1].…”
Section: Introductionmentioning
confidence: 99%
“…photosynthesis inhibitors), algae and macrophyte data may have a similar sensitivity. However, herbicides that inhibit amino acid synthesis and herbicides with an auxin simulation mode of action generally seem to be more toxic to aquatic vascular plants than to algae (Giddings et al, 2013). Currently, knowledge of the MOA of several other types of herbicides is limited.…”
Section: Algae and Aquatic Plantsmentioning
confidence: 99%